2020
DOI: 10.1002/er.5826
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and feasibility analysis of a microscale pin‐fins heat sink of an ultrahigh concentrating photovoltaic system

Abstract: Nowadays, the most recent optical configuration based on Cassegrain and Fresnel lens designs of concentrator photovoltaic(CPV) has shown a race to achieve the ultrahigh concentration ratio. Still, none of those has experimentally shown an optical concentration ratio (GC) beyond 2000 suns. This is because their energy concentration ratios are challenged by the excessive temperature raised throughout the optical stages, which diminishes the efficiency of the solar cell. In this context, this research work aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…The total input power of the incident solar irradiance can be calculated as follows 34 : Qingoodbreak=DNICRηoptAcell, where DNI is the direct normal irradiance, CR is the concentration ratio (×500‐×2000), ηopt is the optical efficiency of primary optics and Acell is the active cell surface area.…”
Section: Design and Methodologymentioning
confidence: 99%
“…The total input power of the incident solar irradiance can be calculated as follows 34 : Qingoodbreak=DNICRηoptAcell, where DNI is the direct normal irradiance, CR is the concentration ratio (×500‐×2000), ηopt is the optical efficiency of primary optics and Acell is the active cell surface area.…”
Section: Design and Methodologymentioning
confidence: 99%
“…Nevertheless, the temperature distribution at the lowest CR of 500Â is more reliable than in the highest CR, as shown in Figure 16, because of the reduction in the heat generated throughout the MJSC. 24 From these outcomes, it could be concluded that the management of the in-line cylindrical arrangement for the UHCPV/T system is expected to be more beneficial, with a drop in the maximum temperature of the MJSC and an enhancement in the temperature distribution uniformity.…”
Section: Temperature Gradient Over the Pin Fins Heat Sinks Backplate ...mentioning
confidence: 99%
“…AlFalah et al 24 carried out an investigation on a passive cooling of an ultra-high concentrating photovoltaic system using pin fin heat sinks. The CR was ranged from 2000Â to 12 000Â.…”
mentioning
confidence: 99%
“…However, the UHCPV modules are exposed to extremely high temperatures experienced by the solar cell or the packed densely array leading to the initiation of cracks in the solar cells, electrical performance degradation and increased the operating costs as a result of employing sophisticated active cooling mechanisms. Recently, Gaeet et al 29 numerically developed and studied three passively cooled inline (PFHS)s for a MJSC under ultra-high CR of up to 12 000. It was found that the circular pin-fins were able to retain the peak operating cell temperature lower than 60 C for a cell surface area of 1 × 1 mm 2 and an ambient temperature of 20 .…”
Section: Review Of Relevant Literaturementioning
confidence: 99%